2015
DOI: 10.1007/s10840-015-0031-3
|View full text |Cite
|
Sign up to set email alerts
|

Abundant epicardial adipose tissue surrounding the left atrium predicts early rather than late recurrence of atrial fibrillation after catheter ablation

Abstract: The abundance of left atrial EAT independently predicted early recurrence after AF ablation; on the contrary, it did not have an impact on late recurrence. Left atrial EAT may have a pro-arrhythmic influence, especially in the early post-ablation phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Most of the articles (7/10) were in the full-text format, while three articles were in the conference abstract [17,19,20]. CT [[15], [16], [17],[19], [20], [21], [22], [23]] and echocardiography [18,24] were the used imaging modalities for EFT measurements. The least sample size was 38 [17], and the largest ones were related to Chao et al, [18] with 283 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the articles (7/10) were in the full-text format, while three articles were in the conference abstract [17,19,20]. CT [[15], [16], [17],[19], [20], [21], [22], [23]] and echocardiography [18,24] were the used imaging modalities for EFT measurements. The least sample size was 38 [17], and the largest ones were related to Chao et al, [18] with 283 patients.…”
Section: Resultsmentioning
confidence: 99%
“…The abundance of EFT and post-ablation AF recurrence was firstly described by Tsao et al; while more than ten different studies have investigated this association up to now [15]. However, these studies have been conducted in different populations, various disease stages (paroxysmal or persistent AF), a variety of EFT measurement methods (computed tomography (CT) or echocardiography), numerous methods of rhythm control strategy (CA or CBA), and diverse intervals of follow-up for AF recurrence [[16], [17], [18], [19], [20], [21], [22], [23], [24]]. The present study was the first attempt to verify the association between AF recurrence and EFT, conducting a meta-analysis of investigations comparing patients with and without AF recurrence after ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Whether EAT has a physiological role to protect these ganglia against mechanical forces due to cardiac contraction has been suggested (266). By contrast, recent clinical data showed that periatrial EAT is an independent predictor of AF recurrence after ablation (157,202,219,296), supporting that EAT may have a pro-arrhythmic influence.…”
Section: Therefore Overlap Between Eat Locations and High Dominant Fmentioning
confidence: 99%
“…Das, et al examined the association between timing of ERAA with the likelihood of PV reconnection at repeat electrophysiology Predictors of ERAA Several predictors of the development of ERAA after AF ablation have been identified and many of these are also predictors of longterm ablation failure. Baseline characteristics such as older age, male gender, presence of structural heart disease, longer AF duration, nonparoxysmal AF type, higher CHA₂DS₂-VASc scores, larger LA size, presence of LV systolic and diastolic dysfunction, and LA epicardial adipose tissue are some of the variables that have been found to predict ERAA and all these are also associated with late arrhythmia recurrence [5]- [12] . Acute procedural findings including incomplete PVI, presence of multiple AF foci, AF inducibility and lack of AF termination during ablation are also associated with ERAA [6], [13], [14] .…”
Section: Original Researchmentioning
confidence: 99%